2017
DOI: 10.3390/su9122376
|View full text |Cite
|
Sign up to set email alerts
|

Does Social Innovation Contribute to Sustainability? The Case of Italian Innovative Start-Ups

Abstract: Start-ups, among other enterprises, play a major role in the development and/or commercialization of new technologies and the development of national economies, given that firms are the innovation locus for an entire society. In Italy, a recent regulatory intervention has focused on start-ups creating a framework where innovative start-ups are defined and regulated. Among innovative start-ups, those with a social vocation are of particular interest, since they are understudied in the literature. Indeed, the ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 57 publications
1
28
0
2
Order By: Relevance
“…Possible indirect effects should be strictly considered and analyzed under the perspective of sustainability. Here, a good point of departure could be the research by Picacarozzi (2017), who analyzed whether socially innovative start-ups contribute to sustainability [76]. In a similar approach, the relationships between the innovators and possible differences depending on the country could also be analyzed.…”
Section: Future Lines Of Researchmentioning
confidence: 99%
“…Possible indirect effects should be strictly considered and analyzed under the perspective of sustainability. Here, a good point of departure could be the research by Picacarozzi (2017), who analyzed whether socially innovative start-ups contribute to sustainability [76]. In a similar approach, the relationships between the innovators and possible differences depending on the country could also be analyzed.…”
Section: Future Lines Of Researchmentioning
confidence: 99%
“…These framework conditions have encouraged universities to design specialised TT organisational units (TTOUs)-such as TT offices (TTOs), incubators and science parks-specifically engaged in TT activities such as patenting, licensing, creation of research-based spin-offs and start-ups [54]. Recently, an institutional arrangement introduced in 2012 by the "Start-up Act" has further strengthened the links between universities and industry [62], generating positive social and economic impacts on local communities [63]. In fact, this is the only framework that regulates innovative start-ups by establishing accurate requirements to determine their innovative character.…”
Section: The Phenomenon Of University Tt In Italy: Evolution or Co-evmentioning
confidence: 99%
“…This definition is consistent with that adopted by NetVal. Similarly, as various definitions of start-ups can be found in the literature, this study considers a start-up as a new company with a high character of innovation (see for example, [62]) that meets the requirements set by Italian Law and that are adopted also by NetVal and PNICube.…”
Section: The Phenomenon Of University Tt In Italy: Evolution or Co-evmentioning
confidence: 99%
“…As said at the beginning of the previous section (see Section 3), the relevance of introducing a specific decree on Italian start-ups was related not only to fostering the overall economic development of the country, but mostly to the start-ups' contribution to sustainable development, technological growth, and youth employment (Piccarozzi, 2017). However, the results of the descriptive statistics reported above showed that the Italian start-up PIJ/Volume 4 -Issue 2/2019 ISSN: 2499-1333 scene/ecosystem seems to be not consistent with the objectives of the legislator.…”
Section: Discussion Implications and Final Remarksmentioning
confidence: 89%